1994
DOI: 10.1007/bf00046390
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in methane flux from rice paddies associated with methane concentration in soil water, rice biomass and temperature, and its modelling

Abstract: To attempt to develop physicochemical and physiological modelling for methane transport from the rhizosphere to the atmosphere through rice plants, methane flux, methane concentration in the soil water, and the biomass of rice were measured in lysimeter rice paddies (2.5 × 4 m, depth 2.0 m) once per week throughout the entire growing season in 1992 at Tsukuba, Japan. The addition of exogenous organic matter (rice straw) or soil amendments with the presence or absence of vegetation were also examined for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 30 publications
7
47
1
Order By: Relevance
“…The soil-texture effect on CH 4 emissions may also be responsible for the lack of a cultivar effect on CH 4 emissions from the clay (NEREC) compared to the silt-loam soil (RREC) in this study (Table 3). In contrast to studies that reported no diurnal variation [6] [14] [15], CH 4 fluxes/estimated emissions differed among measurement times of day for each of the four location-growth stage combinations in the direct-seeded, delayed-flood production system measured in this study. These results were similar to the measured diurnal variations reported previously [2] [4] [6]- [13].…”
Section: Hourly Ch4 Fluxes and Estimated Daily Emissionscontrasting
confidence: 99%
See 1 more Smart Citation
“…The soil-texture effect on CH 4 emissions may also be responsible for the lack of a cultivar effect on CH 4 emissions from the clay (NEREC) compared to the silt-loam soil (RREC) in this study (Table 3). In contrast to studies that reported no diurnal variation [6] [14] [15], CH 4 fluxes/estimated emissions differed among measurement times of day for each of the four location-growth stage combinations in the direct-seeded, delayed-flood production system measured in this study. These results were similar to the measured diurnal variations reported previously [2] [4] [6]- [13].…”
Section: Hourly Ch4 Fluxes and Estimated Daily Emissionscontrasting
confidence: 99%
“…Previous reports indicate diurnal variations (i.e., the amplitude and timing of flux minima and maxima) in CH 4 emissions may also differ over time within the growing season [8] [10] [12]. However, numerous studies have also reported no significant difference in CH 4 emissions between day and night [6] [14] [15]. Differences between cultivars have generally been consistent given the multitude of factors that have been shown to affect CH 4 fluxes and emissions throughout a growing season, such as soil texture [16] [17] [18] [19], fertilizer nutrient source [20], organic soil amendments [8] [12], residue management/previous crop [21] [22] [23] [24], water management scheme [8] [25] [26], and production system [27].…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal pattern of CH 4 emissions increasing once the flood is applied, peaking near heading, then declining prior to flood release has been observed in numerous previous studies [30,32,49,51,53,59,60,61,62] and suggests that root exudates increase during vegetative growth providing substrate for methanogenesis and decrease again during grain fill as resources are translocated to the filling grains. Research conducted by Denier van der Gon et al [63] indicated that CH 4 emissions are related to allocation of photosynthetically derived C between roots and grains and that decreasing translocation of C to grains (i.e., removing florets prior to grain fill) causes an increase in C translocation to roots and an increase in CH 4 emissions.…”
supporting
confidence: 63%
“…The nitrogenous fertilization of paddy soil in this study is about 250 kg N ha −1 , which is equivalent to 107 µg N g −1 d.w.s., assuming an effective soil depth of 20 cm. In addition, methane concentrations of 900-15 000 ppmv were generally detected in paddy soil during rice-growing season (Nouchi et al, 1990(Nouchi et al, , 1994. Therefore, the microcosms were incubated with 100 µg urea-N g −1 d.w.s.…”
Section: Discussionmentioning
confidence: 99%